Jornal das Senhoras: A female journalistic project for the emancipation of Brazilian women - Simon da Silva, Regina (2021)
Argentinian Juana Paula Manso (1819-1875) was born and lived most of her life in one of the most troubled periods in the history of Argentina, and her ideals, daring for the mentality of the time, brought her, among many problems, political persecutions by Juan Manuel de Rosas, which culminated in the family’s exile, first to Uruguay and then to Brazil. In this country, Manso founded and directed, in 1852, Jornal das Senhoras, considered the first Brazilian feminist newspaper, with the clear intention of promoting theemancipation of women. This article, dedicated to the female press, analyzes the dialogue established between the Jornal das Senhoras and the Brazilian readers, seeking to identify elements that foster their illustration and emancipation.